Bounds For the Coefficients of Two New Subclasses of Bi-Univalent Functions - Abdullah, khalid Ibrahim; Mohammed, Nafya H. (Science Journal of University of Zakho, 2022)
This article discusses two new subclasses of the bi-univalent functions category ∑ in the open unit disk . The primary goal of the article is to obtain estimations of the coefficients  and for the functions that are within these two new subclasses.
Keywords: Taylor–Maclaurin Series; Univalent Function; Coefficient Bounds; Bi-univalent Function